2019
DOI: 10.1093/brain/awz324
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sirtuin 1 protein in neurons prevents and reverses experimental diabetic neuropathy

Abstract: In diabetic neuropathy, activation of axonal and sensory neuronal degeneration pathways leads to distal axonopathy. The NAD+-dependent deacetylase enzyme, Sirtuin 1 (SIRT1), can prevent activation of these pathways. Chandrasekaran et al. show that increased expression of SIRT1 in sensory neurons prevents and reverses experimental diabetic neuropathy induced by a high-fat diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 101 publications
1
61
1
Order By: Relevance
“…Several studies demonstrated that sirtuins plays a crucial role on aging, neural disorders and metabolic syndrome ( Brachmann et al, 1995 ; Smith et al, 2000 ). Considering the 7 mammalian sirtuins, the overexpression of SIRT1 and/or its stimulation by certain natural chemical structures (resveratrol for instance), enhance health and life span ( Chandrasekaran et al, 2019 ). SIRT1 modulates several gene components, however there are some priority transcription factors.…”
Section: Sirtuins and Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies demonstrated that sirtuins plays a crucial role on aging, neural disorders and metabolic syndrome ( Brachmann et al, 1995 ; Smith et al, 2000 ). Considering the 7 mammalian sirtuins, the overexpression of SIRT1 and/or its stimulation by certain natural chemical structures (resveratrol for instance), enhance health and life span ( Chandrasekaran et al, 2019 ). SIRT1 modulates several gene components, however there are some priority transcription factors.…”
Section: Sirtuins and Brainmentioning
confidence: 99%
“…The authors suggested a mitophagia associated with NEDD4 that improves mitochondrial breathing capacity, increasing axonal development and reparation. SIRT1 is essential to this route by regulating mitochondrial role in the marginal nerve throughout PGC1-α modulation ( Chandrasekaran et al, 2019 ). Cell culture researches showed that SIRT1 is detect in the nucleus of several cell lines ( Michan and Sinclair, 2007 ) producing deacetylation activity of several transcription factors.…”
Section: Sirtuins and Brainmentioning
confidence: 99%
“…Numerous studies have demonstrated that SIRT1 plays a central role in the regulation of different biological processes, such as mitochondrial biogenesis, oxidation and inflammation. [10][11][12] SIRT1 is activated in many central nervous system diseases, such as subarachnoid haemorrhage and Parkinson's disease. 13 In addition, it has been reported that it is an important…”
mentioning
confidence: 99%
“…NALFD is a pandemic condition involving also the pediatric population [ 174 , 175 ], and regarded as one of the newest risk factors for neurological diseases [ 176 , 177 ], with the life style and the diet regimen being key factors in the CNS pathology progression [ 178 , 179 , 180 ]. The liver and brain appear to be inter-connected at various levels (so-called liver brain axis): (1) A negative correlation between serum bilirubin concentrations and NAFLD stage has been reported [ 75 , 181 , 182 , 183 , 184 ]; (2) the modulation of HMOX1/CO/iron, in turn acting on sirtuin1 (Sirt1—see Table 2 ), a histone deacetylase controlling the adaptive mechanism to disease and the bilirubin transport in both organs [ 89 , 185 , 186 , 187 ] has been also demonstrated; and (3), the liver and brain may be connected by insulin resistance [ 183 ], a feature of the metabolic syndrome whose CNS consequences have been discussed in Section 2.4 .…”
Section: The Yellow Players (Yp)mentioning
confidence: 99%